The Relation among Teeth and Maxillary Dental Arch Dimensions with Anterior Teeth Angulation and Inclination - Sara M. Al-Mashhadany; Jinan Eliewy Saloom; Mohammed Nahidh (The Scientific World Journal)
Objectives. This study aimed at finding out whether anterior teeth angulation and inclination have a relationship with the maxillary teeth and dental arch dimensions. Methods. Fifty study models with normal occlusion were selected from the archive of the Department of Orthodontics at Baghdad Dental Faculty. Maxillary dental arch width and length at different points were determined in addition to measuring anterior teeth angulation, inclination, crown thickness, overjet, overbite, and Bolton’s ratios. The unpaired t-test and Pearson’s correlation coefficient test were used for data analysis. Results. No statistical gender differences were reported in all measurements except the dental arch widths and length where males had significantly higher mean values. Only the maxillary incisor’s inclination showed a direct weak significant correlation with the total arch length. Conclusions. The inclination of upper incisors had a minimal effect on increasing dental arch length.